Transformação da bactéria Bacillus subtilis para análise de endofitismo e promoção do crescimento em plantas de soja e milho - Bueno, Clara Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The use of endophytic microorganisms that promote plant growth in agriculture has been expanding in Brazil and is an excellent strategy to face the challenges of current agriculture, such as reducing production costs with less environmental impacts without detriment to productivity. However, little is known about the factors that can affect endophytism, such as inoculant concentration and mineral fertilization. The present study aimed to evaluate the influence of such factors on soybean and corn crops through treatments with different fertilizer dosages (0 to 100%) and Bacillus subtilis inoculant concentrations (1x102 to 1x1010 CFU mL-1), in addition to transformation of the bacterium with plasmid pGLO. We also tried to understand if there is a relationship between plant growth and the concentration of endophytic B. subtilis. It was found that for soybean crop, the lowest fertilization rates (25 and 50%) were the ones that promoted the largest number of recovered bacteria from the concentration 1x106 CFU mL-1 compared to the control. For corn, inoculations at a dose of 25% fertilization showed better results, which demonstrates that, in addition to the colony modulation capacity performed by plants and bacterial colonies, the fertilizer dose interfered with endophytism. Regarding plant development, the higher inoculated concentrations did not necessarily promote better growth-promoting effects than the concentration of 1x104 CFU mL-1 for both crops, suggesting that higher numbers of endophytic bacteria recovered in the plant do not affect plant growth in the same proportion.

O uso de microrganismos endofíticos promotores de crescimento de plantas na agricultura vem se expandindo no Brasil e é uma excelente estratégia para se enfrentar os desafios da agricultura atual, como redução do custo de produção com menores impactos ambientais sem o detrimento da produtividade. Entretanto, pouco se sabe sobre os fatores que podem afetar o endofitismo, como a concentração do inoculante e a fertilização mineral. O presente estudo teve como objetivo avaliar a influência de tais fatores nas culturas da soja e do milho por meio de tratamentos com diferentes dosagens de adubação (0 a 100%) e concentrações de inoculante de Bacillus subtilis (1x10^2 a 1x10^10 UFC -1), além da transformação da bactéria com plasmídeo pGLO. Também procurou-se entender se há relação entre o crescimento vegetal e a concentração de B. subtilis endofíticos. Verificou-se que para a cultura da soja as doses menores de adubação (25 e 50%) foram as que promoveram o maior número de bactérias recuperadas a partir da concentração 1x10^6 UFC mL-1 em relação ao controle. Para a cultura do milho, inoculações na dose de 25% de adubação apresentaram melhores resultados, demonstrando que além da capacidade de modulação das colônias realizada pelas plantas e bactérias, a dose de fertilizante interferiu no endofitismo. Quanto ao desenvolvimento vegetal, as maiores concentrações inoculadas não promoveram necessariamente melhores efeitos de promoção de crescimento do que a concentração de 1x10^4 UFC mL-1 para ambas culturas, sugerindo que maiores números de bactérias endofíticas recuperadas na planta não afetam o crescimento vegetal na mesma proporção.
Transformation in Bacillus subtilis for endophytic and growth promotion analysis in soybean and corn plants
Keywords: Microbiologia agrícola; Bacillus subtilis; Milho; Soja; Bactérias gram-positivas